'Making of a Strong Woman': a constructivist grounded theory of the experiences of young women around menarche in Papua New Guinea - Elizabeth Maulingin-Gumbaketi; Sarah Larkins; Ronny Gunnarsson; Gun Rembeck; Maxine Whittaker; Michelle Redman-MacLaren (BMC, 2021)
Abstract Background Menarche, the first menstruation, is a significant developmental milestone for females. In Papua New Guinea (PNG), menarche is an important socio-cultural event marking transition from girlhood to womanhood. PNG is a culturally and linguistically diverse nation, with wide-ranging socio-cultural beliefs and practices around menarche. This study explored post-menarcheal women's understanding about body changes and menarche, preparation for menarche, and related cultural beliefs and practices at menarche. Methods A constructivist grounded theory study was conducted with 98 female participants who originated from four PNG provinces: Eastern Highlands Province; East Sepik Province; Milne Bay Province; and National Capital District. The participants were purposively and theoretically sampled, with 10 focus group discussions and six individual interviews conducted using a semi-structured interview guide for data collection. Focus group discussions and interviews were voice recorded and transcribed. Data were inductively analyzed using initial, intermediate and advanced coding, memos and constant comparative methods to develop a theoretical model that explains women's experiences at menarche. Interview participants also identified actions required to improve future experiences of girls at menarche in PNG. Results A grounded theory comprising the core category of 'Making of a Strong Woman' and four interconnecting categories ('Having Baby Sense'; 'Beginning of Learning'; 'Intensifying Learning'; and 'Achieving Womanhood') was constructed. 'Urban' and 'Rural' represented both geographical and socio-cultural intervening conditions that influence the experiences of girls at menarche. Experiences of young women at menarche were rooted in socio-cultural beliefs and practices. Women reported being physically and emotionally distressed and unprepared at onset of menarche. Mothers were considered important support, however, their ability to adequately prepare their daughters is limited by shame and secrecy. Despite these limitations, cultural practices at menarche provided an opportunity for intensive preparation of girls for womanhood. Conclusion Limited pre-menarcheal awareness of the meaning of body changes and menarche of girls was linked to culture of shame and secrecy about open discussion on sexuality. However, traditional cultural practices provide an opportunity for collective support and focused learning for girls. Findings from this study have implications for broader sexual and reproductive health education programs in addressing menstrual health and hygiene in PNG, and the Pacific.